Legal and Ethical Analysis of Advertising for Elective Egg Freezing. Issue 4 (December 2020) - Bayefsky, Michelle J.
This paper reviews common advertising claims by egg freezing companies and evaluates the medical evidence behind those claims. It then surveys legal standards for truth in advertising, including FTC and FDA regulations and the First Amendment right to free speech. Professional standards for medical advertising, such as guidelines published by the American Society for Reproductive Medicine (ASRM), the American College of Obstetricians and Gynecologists (ACOG), and the American Medical Association (AMA), are also summarized. A number of claims, many of which relate to the targeting of younger women for eOC, are found to breach legal and ethical standards for truth in advertising. The ethical implications of misleading advertising claims are also discussed, and the central narrative woven by OC ads — that egg freezing is empowering to women — is examined. The paper concludes that a more balanced approach to the risks and benefits of OC is necessary to truly respect women's autonomy. Moreover, justice requires us to look beyond a medical procedure accessible only to a minority of women in order to address inequities in the workplace.